2023
DOI: 10.1101/2023.01.10.523516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OpaR exerts a dynamic control over c-di-GMP homeostasis andcpsAexpression inV. parahaemolyticusthrough its regulation of ScrC and the trigger phosphodiesterase TpdA

Abstract: The second messenger cyclic dimeric guanosine monophosphate (c-di-GMP) plays a central role in controlling decision making processes of vital importance for the environmental survival of the human pathogenVibrio parahaemolyticus. The mechanisms by which c-di-GMP levels are dynamically controlled inV. parahaemolyticusare poorly understood. Here we report our findings regarding the involvement of OpaR in controlling c-di-GMP metabolism in planktonic and surface-attached cells through controlling the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…The present study shows that H-NS regulation of these phenotypes involves LeuO and their regulation of swarming genes laf and scrABC and biofilm genes cpsA-K and their regulator cpsR . In V. parahaemolyticus , it was shown that OpaR (the HapR homolog) is a positive regulator of CPS production and a negative regulator of swarming motility due to the positive effects of OpaR on c-di-GMP levels and cps expression (12, 2830, 5863) (64). In a Δ opaR mutant, the expression of cpsA , cpsR, and cpsQ is downregulated in V. parahaemolyticus indicating OpaR is a positive regulator of CPS and biofilm formation (14, 60).…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that H-NS regulation of these phenotypes involves LeuO and their regulation of swarming genes laf and scrABC and biofilm genes cpsA-K and their regulator cpsR . In V. parahaemolyticus , it was shown that OpaR (the HapR homolog) is a positive regulator of CPS production and a negative regulator of swarming motility due to the positive effects of OpaR on c-di-GMP levels and cps expression (12, 2830, 5863) (64). In a Δ opaR mutant, the expression of cpsA , cpsR, and cpsQ is downregulated in V. parahaemolyticus indicating OpaR is a positive regulator of CPS and biofilm formation (14, 60).…”
Section: Discussionmentioning
confidence: 99%
“…S6B). This apparent inconsistency cannot simply be explained by ScrABC activation being restricted to surface growth because TpdA, a phosphodiesterase that is highly active in planktonic cells (24), was also capable of driving φVP882 lysogenic conversion of RIMD (Fig. 4C).…”
Section: Discussionmentioning
confidence: 99%
“…Following the same logic as above, perhaps the Qrr sRNAs only drive lysogenic conversion in planktonic cells because their downstream target is a planktonic-specific factor(s). Possessing surface growth- and planktonic growth-specific intermediate factors could provide RIMD an effective mechanism to confine the influences of the Qrr sRNAs and c-di-GMP abundance to their respective physical contexts despite both the Qrr sRNAs and c-di-GMP having other roles in planktonic and surface-associated cells (22,24,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation